Harry Potter and the sorcerer's stone - Rowling, J. K. (Scholastic Inc., 2018)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Wizards and Witches.